Implementation of MRAC, SVMPC and PID control based on direct digital control application for dc servomotor - Mohamad Saleh, Saleha (2005)
The project focused on speed control of DC servomotor under load variation using Direct Digital Control technique. The main objective is to design and develop GUI software for speed control experiment, where Single Variable Model Predictive Control (SVMPC), Model Reference Adaptive Control (MRAC) and PID controllers’ design approaches has been applied. The main purpose of using the SVMPC is to achieve perfect control using an Internal Model Control (IMC) strategy. The desired behavior of the adaptive controller is expressed by utilizing reference model, and the algorithms have been realized using the Lyapunov method and MIT rules. The Direct Digital Control approach is selected to replace the conventional method regarding on controlling the speed of DC motor because of its advantages in terms of cost reduction, simplicity, flexibility and give better performance than previous one. The original speed control experiment is conducted and data is recorded. Based on the information that been gathered, the controllers have been designed and the system is simulated using MATLAB to analyze their initial performance. The computer is connected to MS150 Modular Servo System via AX5412 data acquisition card and Microsoft Visual Basic 6.0 is used to conduct the experiment. Field-testing is implemented to compare the results between the original and modified system within three types of controller. Finally, the performance of the system is analyzed and validation is done in terms of time response, robustness and percentage of error